A user adaptable user interface model to support ubiquitous user access to EIS style applications - Davis, Jon; Tierney, Andrew; Chang, Elizabeth (IEEE, 2005)
The user interface for computer applications is typically hard coded and offers minimal flexibility for user customisation. In this paper we list and discuss several requirements for application user interfaces that offer widespread application accessibility, access across international boundaries, and that support individualisation by normal users (without the need for specific software customization by developers). We review related works in XML based user interface deployment and identify shortcomings, and present a solution that we name the Web service based Adaptable User Interface (WAUI). The major features of the WAUI are; the decoupling of the traditional user interface from both the execution platform and the rest of the application layers by the use of web services, and providing for an automated user interface adaptation capability based on; the user?s selected cultural and internationalization options, the user?s preferences for alternative visual display objects, and the optional preferences that a user defines for modifying the function and layout of application forms and display objects.